Regional anaesthesia for postoperative pain management after liver resection - Trepenaitis, Darius; Česnaitis, Tadas; Macas, Andrius (Acta medica Lituanica, 2012)
Background. Pain is the most common complication in the postoperative period. If adequate treatment is not taken, it can transform to chronic pain. Postoperative pain brings a lot of social, psychological and financial problems for patients and their families. Materials and methods. This prospective study included 30 patients after laparatomic liver resection operation. Patients were randomly assign ed to Infiltrated or Control groups. An infiltration of 40 ml levobupivacaine 0.25% solution to the operation cut edges was performed to the Infiltrated group. The pain was evaluated using the numerical rating scale after 2, 5, 12, 24, 48 hours and 1 month after the operation. Our aim was to determine the effect of local anesthesia in the operation wound. The total usage of morphine and any side effects were registered. Results. A statistically significant reduction in pain was observed in the Infiltrated group in all evaluation periods. Opioids usage was higher in the Control group almost by 4 times and adverse effects were 9 to 1 compared to the Infiltrated group. Conclusions. Surgical wound infiltration with local anesthetic for postoperative pain management after liver resection operations has a positive effect on postoperative pain reduction and leads to lesser usage of opioid analgetics. As a result, there is a less chance of opioids induced adverse effects.